New and significant bird records for Solor, Adonara, and Lembata (Lomblen) islands, Lesser Sundas - Mark Schellekens; Colin R Trainor; Gaudensius U.U.B Duhan (KUKILA, 2011)
The birds of the island of Solor were last investigated about 150 years ago when Charles Allen, an assistant of Lord Alfred Wallace, collected four species. During a one-day visit in 2005 the first author recorded an additional 47 species, including 33 resident land birds. A total of 37 species, including ten new island records, were observed on Adonara over a 2-day period in January 2005 and a brief visit in 2009. The second author recorded 33 species over four days on Lembata, including seven new island records. Few of the new island records for these three islands involved resident forest birds. A notable exception was the Oriental Dwarf Kingfisher Ceyx erythacus on Lembata, extending its easterly limits. The avifaunas of Solor, Adonara and Lembata are species-poor subsets of the Flores mainland avifauna; only three species - Olive-headed Lorikeet Trichoglossus euteles (Adonara, Lembata), Common Cicadabird Coracina tenuirostris (Lembata) and Broad-billed Flycatcher Myiagra ruficollis (Lembata) – are absent from Flores. The forest avifauna of these islands remains poorly known and deserves further attention.